Inclusion complex of tamibarotene with hydroxypropyl-β-cyclodextrin: Preparation, characterization, in-vitro and in-vivo evaluation - Ying Yang; Jinhua Gao; Xiaoyu Ma; Guihua Huang (Elsevier, 2017)
The goal of this study was to improve the solubility and oral bioavailability of tamibarotene by complexing it with hydroxypropyl-β-cyclodextrin (HP-β-CD). The inclusion complex of tamibarotene with hydroxypropyl-β-cyclodextrin (Am80-HP-β-CD) was prepared through a freeze-drying method at the mole ratio of 1:1 (Am80: HP-β-CD). Fourier transform infrared spectroscopy (FT-IR) and differential scanning calorimetry (DSC) indicated the formation of Am80-HP-β-CD. In vitro dissolution studies showed that the solubility and dissolution percentage of Am80-HP-β-CD was improved substantially compared to Am80. An improved dissolution with approximately 97% drug release in 3 min was observed, in comparison with Am80 with approximately 60% release in 45 min. In vivo studies indicated that the AUC0-∞ has increased 2.79 times and the Cmax 4.37 times after the formation of inclusion complex. The decrease of tmax indicated the Am80-HP-β-CD inclusion complex can be absorbed into blood faster. In short, the solubility and bio-availability of Am80 has notably increased with the complexation of HP-β-CD. Therefore, using the inclusion technique is a promising method to improve the solubility of insoluble drugs.